Forensic case histories : understanding serious offending behaviour in men - Craissati, Jackie (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Forensic Case Histories: Understanding Serious Offending Behaviour in Men examines men's violent and sexual offending behaviors, outlined through a series of real offender narratives, from a psychological perspective and in an accessible manner that will engage any audience, from the criminology-intrigued layperson to the specialist in the field. This unique and conversational text thinks psychologically about serious crime, offering a compilation of men's narratives that explore their life experiences and the ways in which these experiences influence their behavior in adulthood. Each chapter addresses a particular theme, covering frequently asked questions in the field such as, "How can an apparently motiveless offence have meaning?" and "Is psychopathy a personality disorder, and why do we struggle to treat individuals with such traits?" The narratives of individuals who offend are central to the discussion, but the chapters each draw on the relevant facts from the research literature and highlight key learning points. Many chapters also feature "Further Reading" sections to expand readers' knowledge. Both educational and accessible, Forensic Case Histories will appeal not only to specialists but to any layperson curious to understand more about criminal acts. It is especially valuable to students and instructors of criminal justice, mental health, and related fields"--
OCLC-licensed vendor bibliographic record.
Keywords: Sex offenders -- Psychology -- Case studies; Sex offenders -- Rehabilitation -- Case studies; Psychosexual disorders -- Case studies; Criminal psychology -- Case studies; PSYCHOLOGY / Forensic Psychology; PSYCHOLOGY / Applied Psychology